Pengaruh Riwayat Pemberian ASI Eksklusif, Sanitasi Dan Pola Asuh Orangtua Terhadap Stunting Pada Balita Di Wilayah Kerja Puskesmas Kelurahan Pulau Panggang Kepulauan Seribu Tahun 2023 - Rima Ida; Susaldi Susaldi; Agustina Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
The prevalence of stunting in the world is still relatively high, including in Indonesia and the Thousand Islands where the prevalence of stunting under five in the Thousand Islands Region is 27.1%. The purpose of this study was to determine the effect of a history of exclusive breastfeeding, sanitation and parenting styles on stunting in toddlers at the Puskesmas in the Panggang Island Sub-District, Seribu Islands in 2023. The type of research used in this study was to use a quantitative analytical descriptive method. The research design used was a cross-sectional or cross-sectional study. This research was conducted in the Thousand Islands Region in 2023. The time of the research was January – February 2023. This research was focused on parents who had toddlers in the Working Area of ​​the Panggang Island Village District Health Center in Thousand Islands in 2023 as many as 559 people. The required sample is 85 respondents. The sampling technique for respondents used a simple random sampling technique. The research instrument used to collect data is by using a questionnaire or questionnaire and collecting data by observation. Based on the results of the study, the effect of history of exclusive breastfeeding (P value = 0.001), sanitation (P value = 0.000) and parenting style (P value = 0.000) on stunting. The conclusion is that there is an effect of a history of exclusive breastfeeding, sanitation and parenting styles on stunting in toddlers in the Working Area of ​​the Panggang Island Village Health Center Seribu Islands in 2023.